Knowledge Internationalization and Visibility - López López, Wilson; Pontificia Universidad Javeriana (2010)
In any epistemological perspective, the community cannot account for any knowledge which is not made visible, which remains unpublished, which is not read by society. This apparent obviousness has many shades of meaning, especially in Social Sciences: on the one hand, there is a strong discussion on the lesser value given by international journals to local knowledge, despite local issues gaining more importance and interest in research communities worldwide. On the other, some state that global hegemonic knowledge opposes local knowledge, which is reinforced by the fact that citation analyses show that the main sources in Social Science and Psychology in Latin America are North American and European journals publishing this hegemonic knowledge. Therefore, it is important to ask whether there is more than demagogy in this discussion. What data on Latin American journal visibility show is that, the more international the contents, the more visible they are. We need to clarify what “International” means, since journal Internationality has many elements to it: international scientific, editorial and peer-reviewer committees, content internationality, that is, a proportion of articles written in International collaboration or authored by people from many countries; and user internationalization. Network users are local, national, regional and global – I think this taxonomy will soon disappear, now that some users live longer on global networks than in their own locations. Journals publishing knowledge in Social Sciences are more sensitive to this local/global debate, and Editors are caught in the middle of this tension. Nevertheless, the problem must be correctly stated to avoid using easy discourses which are of no use and are basically empty words. Our journal has developed strategies in the local, regional and global scopes. Our committees feature a varied representation, and prestigious researchers with International visibility have entered them in the last few months. We want to take this opportunity to welcome some of them, including Arthur Cantos (Rosalind Franklin University), Friedrich Wilkening (Universität Zürich), João Manuel Salgado (ISMAI Portugal), Juan Preciado (City University of New York), Merry Bullock (APA), Robert Sternberg (Tufts University), Sheri Levy (Stony Brook University), Hipólito Marrero (Universidad de la Laguna), and Wilhelm Kempf (Universität Konstanz). We have also enhanced our collaborators list locally, regionally and globally. They help with visibility and communication developments in our website. We welcome Marco Peña (Perú), Juan Carlos Canga (Venezuela), Felix Neto (Portugal), Alfonso Barca (España), Hugo Klappenbach (Argentina), Antonio Maldonado (España), and Marcelo Urrá (Chile). In this same direction, a note in APA’s website has recently appeared featuring our Journal, and an article on our new website is being published by the journal Scholarly and Research Communication. It is important to emphasize that Universitas Psychologica has a growing participation of articles in collaboration, both interinstitutional and international, from countries in the region and outside. Last, it is clear that there is an agenda associated to climbing in impact indexes in the systems providing this information. This has been previously commented in other editorials. It is clear that an editor, especially in our context, gives an important weight to articles involving international and inter-institutional collaboration, since these articles may create more visibility opportunities and potentially more visits and citations to the journal. Wilson López López Editor